The Enhancement of Biogas Production from Food Waste by Using Two-stage Upflow Anaerobic Sludge Blanket (UASB) Reactor at Mesophilic Temperature - Intanoo, Patcharee; Somrit, Kanjana (YRU Journal of Science and Technology, 2025)
At present, the demand for energy is increasing, particularly for fossil fuels, which contrasts with the limited availability of natural resources. To sustainably meet this growing demand, alternative energy production technologies with properties similar to fossil fuels have been developed. One such technology is the production of biogas from food waste using a two-stage upflow anaerobic sludge blanket (UASB) reactor under mesophilic conditions, maintained at a constant temperature of 37°C and a pH range between 4.50–7.50 with a recycle ratio at 1:1. The study on biogas production from food waste using the two-stage UASB reactor was operated at different COD loading rate ranging from 10.54 to 26.40 kg/m3d based on working volume of 5 liter and 8.10 to 21.60 kg/m3d based on working volume of 16 liter. From the study, it revealed that at an optimal COD loading rate of 21.07 and 18.90 kg/m3d based on working volume of 5 and 16 liter, respectively, the system gave the highest methane production performance. It performed in term of the maximum methane production rate of 33.85 ml/d, with a specific methane production rate of 1.58 ml CH4/l d (or 4.19 ml CH4/g bacteria d) and a maximum methane yield of 0.114 ml CH4/CODapplied (or 2.38 ml CH4/CODremoved). This is corresponding to the maximum COD removal of 45.14 %.